Automated gait analysis indicates efficacy of T-type calcium channel inhibition for mitigation of disrupted calcium signalling in an SCA5 mouse model - Daumante Suminaite; Nurul Fatihah Talib; Sophie Jane Pettegree; Han Chew Gaelan Tan; Yvonne Louise Odey; Emma Margaret Perkins; Alastair Robert Lyndon; Paul Andrew Skehel; Mandy Jackson (Scientific Reports)
Abstract Spinocerebellar ataxias (SCAs) are dominantly inherited progressive neurodegenerative disorders which to date have no effective treatment. SCA5 arises from mutations in the β-III spectrin gene (SPTBN2) with mice lacking β-III spectrin function (β-III−/−) mirroring the human clinical phenotype. This study finds evidence for dysregulated calcium homeostasis in β-III−/− mice as evidenced by enhanced auto-phosphorylation of calcium-calmodulin dependent kinase II (CaMKII), a major calcium sensor in cells, and phosphorylation of several CaMKII targets. Mibefradil, an inhibitor of calcium channels, was also found to improve disordered β-III−/− Purkinje cell dendritic morphology in vitro. However, key to evaluation of potential treatments in vivo is the ability to assess relevant changes at later stages of disease in β-III−/− mice, which has previously been problematic. Here the CatWalk XT system was successful in detecting differences in both truncal stability and interlimb coordination across the disease course of β-III−/− mice. Building on these findings CatWalk analysis showed trimethadione, a selective T-type calcium channel inhibitor, but not riluzole nor verapamil, significantly improved interlimb coordination of 8-month-old β-III−/− mice. These findings highlight the CatWalk XT system as a valuable tool to assess age-dependence of motor function and that modulation of T-type calcium channels has therapeutic potential for SCAs.